Heat stress effect and given of hexane extract jaloh bark (Salix tetrasperma Roxb) to cortisol level, triiodothyronine and hematology profile of broiler chickens - Sugito .; W Manalu; D.A Astuti; E Handharyani; Chairul . (Indonesian Center for Animal Research and Development (ICARD), 2007)
Plasma concentration of cortisol and hematological profile on broiler chickens can be used as heat stress indicators. This study was conducted to investigate the effect of administration of n-hexane extract of jaloh bark (EHJ) on heat-stressed broiler chicken. Thirty broilers, aged 20 days (strain Cobb), were randomly divided into 5 groups. The first group was external control (tCP) i.e. chickens without heat stress and without EHJ administration. The second group was internal control (CP) representing chickens given heat stress without EHJ administration. The third, fourth, and fifth groups were chickens given heat stress and EHJ administration at doses 5, 10, and 20 mg/kg BW, respectively symbolized as CP+EHJ5, CP+EHJ10, and CP+EHJ20. The experimental broilers were exposed to heat stress in constant temperature of 33 ± 1oC for 4 hours daily for 5 and 10 days. The EHJ was given 1 hour before temperature in the cage was raised and was given in daily basis. The level of cortisol in feces were measured from feces collected 1-2 hours before treatment, 3-4 hours after heat stress exposure, and 2-3 hours after heat stress termination. This research indicated that heat stress at temperature 33 ± 1oC during 2 and 4 hours increased cortisol excretion in feces (P<0.05) and increased ratio H : L (P<0.10). The EHJ at dose of 10 mg/kg BW relatively gave more protection from heat stress impact on broilers. Key Words: Cortisol, Triiodothyronine, Heat Stress, Salix, Hematology